Group Positive Psychotherapy Improves Resilience of Gay People Living with HIV/AIDS - Yunanto, Taufik Akbar Rizqi; Hasanat, Nida Ul (UI Scholars Hub, 2019)
Gay people living with Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) face two stigmas, being gay and having HIV/AIDS, thus making their daily lives very complicated. To survive their life challenges, they need strong resilience. This study examined the sustainability effects of Group Positive Psychotherapy in improving the resilience of gay people living with HIV/AIDS. Participants were 18 gay people (9 each in experimental and control groups) living with HIV/AIDS and experiencing resilience problems. The study’s design was quasiexperimental, with an untreated control group and pretest and posttest dependent samples using switching replications. The instruments used were the Resilience Scale, the Positive Psychotherapy Inventory (PPTI), and the Day Reconstruction Method (DRM). Besides qualitative analysis, quantitative analysis was conducted through statistical testing using the Mann-Whitney U Test. Results showed that Group Positive Psychotherapy significantly improved participants’ resilience (U = 0.000; p < 0.01), and its effects lasted for at least two weeks post-intervention. In this study, the Group Positive Psychotherapy sessions on “three good things” and “savoring” proved most effective in improving the resilience of gay people living with HIV/AIDS. Group Positive Psychotherapy also effectively reinforced groups as a positive forum for sharing.